PERSEPSI DAN PREFERENSI IKLAN MEMPENGARUHI NIAT BELI ANAK PADA PRODUK MAKANAN RINGAN - Sumarwan, Ujang; Simanjuntak, Megawati; Yurita, Yurita (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2012)
This research was to analyze the differences between perception, preference, and purchase intentions based on treatment and gender; influence of perception, preference, and consumption experience toward purchase intentions of children; influence of gender and treatment toward perception, preference, and purchasing intentions of children at snack products. This study use a factorial experiment design with two variables that is treatment (treatment 1 (T1): advertising exposure followed by consumer test, treatment 2 (T2): consumer test followed by advertising exposure) and gender (male and female). This research involved 60 school-aged children that was choosed by random sampling. The Independent sample t-test showed that child’s perception had significant difference significant between gender in treatment 1 and between treatment. Multiple linear regression analysis showed that perception, preference, and consumption experience influence significantly on purchasing intention of children. Two-Way ANOVA analysis also showed that perception was influenced by gender and interaction between gender and treatment.